Peningkatan Kualitas Cita Rasa Makanan Rumah Sakit untuk Mempercepat Penyembuhan Pasien - Liber Liber; Nuri Andarwulan; Dede Robiatul Adawiyah (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2014)
Provision of nutrition and ensuring its suf cient consumption in hospital is one key aspect in the care of hospitalized patients. The objectives of this study were: (1) to identify the kind of foods and im- provement of its sensory quality in the hospital menu, (2) to analyze the effect of improved sensory quality on consumption and nutrient intake of patients, health status, and duration of medical treatment. Different kinds of food were identi ed from a 10 days hospital menu by hospital chef and nutritionist. Their sensory quality was improved by adding commercial seasoning powder. This intervention study was conducted as a blind random control trial at a state hospital involving 100 TBC patients. The food consumption and nutrient intake for patients given seasoned food showed signi cant increase (t-test p= 0.000 for P< 0.05) compared with control (1574.2±10.9 g/day vs. 1355.4±51.7 g/day respectively). Whereas nutrient intake of patients receiving intervention was higher: energy (2213.3±16.8 kcal), protein (83±1.8 g), fat (62.5±0.7 g), carbohydrate (331±13 g), vitamin C (89.3±3.4 mg) and zinc (9.5±0.2 mg). However, iron intake of showed no difference (t-test p= 0.566 for P> 0.05). Furthermore, the body weight and BMI of patients receiving intervention increased by (1.3±1 kg) and (0.5±0.4); while control patients weight and BMI decreased by (-1,2±1.1 kg) and (-4.3±0.4), respectively. The duration of treatment in hospital for patients receving seasoned food was 4.5 days shorter than control. Thus, improving sensory quality of hospital foods increased the nutrient intake and decreased duration of medical treatment in hospitalized patients.